THE USE OF COOPERATIVE LEARNING TO ENHANCE STUDENTS SPEAKING ABILITY IN ONLINE CLASSROOM - Purba, Jane Theakara Naomi BR (RETAIN, 2022)
This study aims to describe students’ participants when the teacher implements cooperative learning in the classroom. Moreover, this study is aimed to investigate the effectiveness of cooperative learning that is used by the student to increase their ability to speak in English. This study used the qualitative method to get the data. The subject of the study is one group that consists of 5 senior high school students who are actively working in a group. The data were gathered through field notes which were used to take note of all of the information about how the teacher’s and the student's behavior in the classroom to discover the implementation of cooperative learning by the teacher. Then, the questionnaire followed by an interview session was used to get more data from the following question of the questionnaire. This research was conducted in two meetings. The finding of this study showed that cooperative learning is still not effective to implement by the teacher in the online classroom. it showed from fewer students who asked questions during the learning activity. In explaining the field note, the teacher only gives the assignment without monitoring the students’ group works. Then, students must use various media for groups working outside the online classroom that is less of teacher control. However, from the questionnaire followed by the interview, the student claimed that cooperative learning was helped them to reduce their problem of speaking. They stated that from cooperative learning, they could practice their speaking more and get feedback for the mistakes also motivation. They implement cooperative learning through virtual meeting applications and group chatting in WhatsApp features such as voice notes or video calls. The student also gives feedback and advice as a response to their participation in the cooperative learning activity. In sum, the finding of this study showed that the implementation of cooperative learning in an online class was still not suitable but, effective for students’ regular work-study. Keywords: cooperative learning, Senior High School, Speaking.